Implementation of BIM Methodology in Calculating Column and Beam Structures for the Main Lecture Building of P4T Empat Lawang Regency - I Putu Leo Pramana; Betty Susanti; Bimo Brata Adhitya (International Journal of Health Engineering and Technology, 2024)
Reliable volume estimation and BOQ are indispensable for streamlined construction planning. Errors and omissions in manual calculations and communication result in cost overruns, delays, and ultimately lead to conflicts and disputes among the parties involved in the project. This process is time-consuming and prone to human error. One way to improve efficiency is to implement Building Information Modeling (BIM) in volume estimation and BOQ calculations to enhance work effectiveness. Autodesk Revit is one software that can assist in 3D modeling and accurate volume calculations. This research discusses how BIM can aid in the process of calculating the volume of structural columns and beams for the Main Lecture Hall in the Integrated Agricultural Research and Development Center (P4T). Compared to conventional methods, the research results indicate that the implementation of BIM in this project has provided significant benefits in terms of efficiency, improved calculation accuracy, material usage, and cost savings. With the optimization of concrete usage in structural columns and beams by approximately 26.92% and reinforcement volume by approximately 13.55%, BIM has proven to provide significant added value to the project.